The analysis of computer technology development of aviation personnel training - Глухих, И. Н.; Гузий, Н. Н.; Игнатов, В. А. (Proceedings of National Aviation University (archive), 1999)
Surveyed is analytical review of computer technology development of professional training of pilots and technical personnel of civil aviation. Determined are the peculiarities of cognitive training system. Demonstrated are perspective directions of development of training computer systems on the basis of structural and functional integration of programming means